Teaching Materials Using the Project Based Learning Model on Learning Outcomes of Elementary School Students - Tukiyo; Triyono; Haryono, Purwo; Tasari; Suwartini, Sri (Journal for Lesson and Learning Studies, 2024)
Learning tools must support teacher and student learning to achieve learning outcomes. The absence of teaching materials will be a barrier to good learning outcomes. Educators are asked to actively participate in creating inventive learning tools, including interesting teaching materials, with this free curriculum. Students who enjoy learning will help teachers in the learning process. The aim of this research is to analyze how much influence teaching materials have on the learning outcomes of fifth grade elementary school students. The method used is quantitative. The instruments used were observations, interviews and questionnaires. Data analysis techniques include reliability testing, validity testing, analysis prerequisite testing, and hypothesis testing. The sample consisted of 32 students who were in class V of elementary school. The results of this research showed that the influence of teaching materials was 61% on student learning outcomes. Meanwhile, 39% was influenced by factors outside this research. It was concluded that the use of teaching materials that use learning models influences student learning outcomes.